Current Pest Status and Management Practices for Systena frontalis (Coleoptera: Chrysomelidae) in Ornamental Plants in the Eastern United States: An Online Survey. Issue 1 (22nd April 2021) - Joseph, Shimat V; Chong, Juang-Horng; Campbell, Benjamin; Kunkel, Brian; Lauderdale, Danny; Jones, Stacey; Gill, Stanton; Chen, Yan; Schultz, Peter; Held, David; Hale, Frank; Dale, Adam; et al.
Abstract: Systena frontalis (F.) (Coleoptera: Chrysomelidae) is an important pest in ornamental plant nurseries in the United States. Information on current pest status and management practices employed by nurseries, garden centers, and landscape care operations are crucial to developing an effective research and extension program for ornamental crops. An online survey was developed and administered by the research team in 2020 to gather data on pest status and current pest management practices. The questionnaire included three focus areas: 1) participant (location, industry type, or operating area); 2) pest status indicators (incidence, affected crops, and estimated loss); and 3) common pest management practices. The questionnaire was distributed to stakeholders via e-mail lists, newsletters, and blogs. Seventy-five responses were received; 82.6% of which were from wholesale nursery operators in 19 U.S. states and 1 Canadian province. For most respondents (72%), damage recurred yearly in the past 10 yr and persisted from April to October. About 56% of respondents reported damage on more than five host plant species (with Hydrangea spp. being the most frequently identified) representing approximately 25% of the total number of plants grown in the facilities. Presence of S. frontalis is being monitored mainly through visual inspection of foliage for adult presence or foliage damage (100%), with scouting occurring mainly at weekly intervals (57%). The majority of respondents used broad-spectrum insecticides (such as pyrethroids) for adult (89%) and larval control (47%). We estimated that a grower spends USD$1, 637/ha/yr on insecticides and labor for monitoring and implementing S. frontalis management.